2015
DOI: 10.12962/j24433527.v8i1.1239
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teachers’ Experiential Learning and Reflection for Enhanching their Autonomous Personal and Professional Development

Abstract: Today's teachers are not only teaching, but they have to fulfill various educational roles. This situation demands teachers to learn continuously. They should develop themselves to improve students' achievement. To grow continuously, teachers should not just wait for formal, instructed or top-down training or learning. They should be autonomous and self directed. They should be aware and analyze what they need and how they should obtain knowledge or skill that they need. Autonomous teachers learn by reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Beyond serving as a trigger for reflection, interviewees also discussed the importance of dialogue in building community and providing support among faculty members. This is consistent with findings from other studies such as Hoekstra andKorthagen (2011), andSuryani andWidyastuti (2015). According to Suryani and Widyastuti (2015), without the sharing of ideas with others, teachers may become absorbed in their daily teaching routine and miss important aspects of their teaching practice.…”
Section: Interactions With Peers and Supervisorssupporting
confidence: 90%
See 3 more Smart Citations
“…Beyond serving as a trigger for reflection, interviewees also discussed the importance of dialogue in building community and providing support among faculty members. This is consistent with findings from other studies such as Hoekstra andKorthagen (2011), andSuryani andWidyastuti (2015). According to Suryani and Widyastuti (2015), without the sharing of ideas with others, teachers may become absorbed in their daily teaching routine and miss important aspects of their teaching practice.…”
Section: Interactions With Peers and Supervisorssupporting
confidence: 90%
“…This discrepancy leads to inner discomfort" (Pammer et al, 2011, p. 48). For example, the study by Suryani and Widyastuti (2015) found three main sources of reflection and learning for teachers. Namely, their teaching experiences, sharing ideas in professional communities, and researching.…”
Section: Views Of Reflectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in order to improve student achievement, today's circumstances need instructors who are also continuing to learn, develop, and evolve. They should be aware of what they require and how they will obtain the information or skills they desire, and they should reflect on their everyday experiences to enhance their teaching and learning skills (Suryani & Widyastuti, 2015).…”
Section: Introductionmentioning
confidence: 99%